When performativity meets agency: how early career teachers struggle to reconcile competing agendas to become 'quality' teachers. Issue 5 (4th July 2021) - Sullivan, Anna; Johnson, Bruce; Simons, Michele; Tippett, Neil
ABSTRACT: Early career teachers are increasingly required to be 'classroom ready' upon graduation and to demonstrate capabilities that match their more experienced colleagues. They are also joining a profession that is characterised by increased scrutiny and accountability driven by standards that seek to identify the hallmarks of good teaching. This agenda, constructed around a discourse of 'quality', has created dilemmas for early career teachers. However, little is known about how early career teachers navigate these pressures as they begin their careers. This article reports on a study that sought high-achieving graduate teachers' perceptions of teacher quality and how they assessed their own practices within a 'quality' framework. The study found that high-achieving early career teachers wrestle with their perceptions of what a 'good' teacher might be and do, and how this contrasts with official representations of a 'quality teacher', and that they frequently 'govern' themselves using the regulations and discourses related to 'the quality teacher'. We argue that broader conceptualisations of teacher quality are needed to enable early career teachers to develop as agentic professionals.